Torsional Vibration Suppression in Multi-Condition Electric Propulsion Systems Through Harmonic Current Modulation - Hanjie Jia; Guanghong Hu; Xiangyang Xu; Dong Liang; Changzhao Liu (Actuators)
Electric helicopters represent a pivotal component in the advancement of urban air mobility (UAM), with considerable potential for future development. The electric propulsion system (EPS) is the core component of these systems. However, the inherent complexities of electromechanical coupling can induce excessive torsional vibrations, potentially compromising operational comfort and even threatening flight safety. This study proposes an active torsional vibration suppression method for EPS that explicitly incorporates electromechanical coupling characteristics. A nonlinear dynamic model has been developed, accounting for time-varying meshing stiffness, meshing errors, and multi-harmonic motor excitation. The motor and transmission system models are coupled using torsional angular displacement. A harmonic current command generation algorithm is then formulated, based on the analysis of harmonic torque-to-current transmission characteristics. To achieve dynamic tracking and the real-time compensation of high-order harmonic currents under non-steady-state conditions, a high-order resonant controller with frequency-domain decoupling characteristics was designed. The efficacy of the proposed harmonic current modulation is verified through simulations, showing an effective reduction of torsional vibrations in the EPS under both steady-state and non-steady-state conditions. It decreases the peak dynamic meshing force by 4.17% and the sixth harmonic amplitude by 88.15%, while mitigating overshoot and accelerating vibration attenuation during speed regulation. The proposed harmonic current modulation method provides a practical solution for mitigating torsional vibrations in electric propulsion systems, enhancing the comfort, reliability, and safety of electric helicopters.